Nanoantenna-assisted plasmonic enhancement of IR absorption of vibrational modes of organic molecules - Milekhin, Alexander G.; Cherkasova, Olga; Kuznetsov, Sergei A.; Milekhin, Ilya A.; Rodyakina, Ekatherina E.; Latyshev, Alexander V.; Banerjee, Sreetama; Salvan, Georgeta; Zahn, Dietrich R. T. (Beilstein Journal of Nanotechnology, 2017)
Nanoantenna-assisted plasmonic enhancement of IR absorption and Raman scattering was employed for studying the vibrational modes in organic molecules. Ultrathin cobalt phthalocyanine films (3 nm) were deposited on Au nanoantenna arrays with specified structural parameters. The deposited organic films reveal the enhancement of both Raman scattering and IR absorption vibrational modes. To extend the possibility of implementing surface-enhanced infrared absorption (SEIRA) for biological applications, the detection and analysis of the steroid hormone cortisol was demonstrated.
Keywords: cobalt phthalocyanine; cortisol; localized surface plasmon resonance; metal nanoantennas; Raman scattering; surface-enhanced infrared absorption (SEIRA)

(untitled) - Wang, L.; Yoon, M.-H.; Lu, G.; Yang, Y.; Facchetti, A.; Marks, T. J. (Nat. Mater., 2006)

(untitled) - Zhang, C.; Chen, P.; Hu, W. (Chem. Soc. Rev., 2015)

(untitled) - Dediu, V. A.; Hueso, L. E.; Bergenti, I.; Taliani, C. (Nat. Mater., 2009)

(untitled) - Gu, H.; Zhang, X.; Wei, H.; Huang, Y.; Wei, S.; Guo, Z. (Chem. Soc. Rev., 2013)

(untitled) - Robaschik, P.; Siles, P. F.; Bülz, D.; Richter, P.; Monecke, M.; Fronk, M.; Klyatskaya, S.; Grimm, D.; Schmidt, O. G.; Ruben, M.; Zahn, D. R. T.; Salvan, G. (Beilstein J. Nanotechnol., 2014)

(untitled) - Barraud, C.; Bouzehouane, K.; Deranlot, C.; Kim, D. J.; Rakshit, R.; Shi, S.; Arabski, J.; Bowen, M.; Beaurepaire, E.; Boukari, S.; Seneor, P.; Mattana, R. (Dalton Trans., 2016)

(untitled) - Lach, S.; Altenhof, A.; Tarafder, K.; Schmitt, F.; Ali, M. E.; Vogel, M.; Sauther, J.; Oppeneer, P. M.; Ziegler, C. (Adv. Funct. Mater., 2012)

(untitled) - Serri, M.; Wu, W.; Fleet, L. R.; Harrison, N. M.; Hirjibehedin, C. F.; Kay, C. W. M.; Fisher, A. J.; Aeppli, G.; Heutz, S. (Nat. Commun., 2014)

(untitled) - Schmaus, S.; Bagrets, A.; Nahas, Y.; Yamada, T. K.; Bork, A.; Bowen, M.; Beaurepaire, E.; Evers, F.; Wulfhekel, W. (Nat. Nanotechnol., 2011)

(untitled) - Annese, E.; Fujii, J.; Vobornik, I.; Panaccione, G.; Rossi, G. (Phys. Rev. B, 2011)

(untitled) - Larson, T. A.; Bankson, J.; Aaron, J.; Sokolov, K. (Nanotechnology, 2007)

Nanoantenna: Plasmon-Enhanced Spectroscopies for Biotechnological Applications - de la Chapelle, M. L.; Pucci, A. (Pan Stanford Publishing Pte. Ltd., 2013)

Surface-enhanced Vibrational Spectroscopy - Aroca, R. (John Wiley & Sons, 2006)

(untitled) - Steinle, T.; Neubrech, F.; Steinmann, A.; Yin, X.; Giessen, H. (Opt. Express, 2015)

Surface–Enhanced Raman Scattering: Physics and Applications - Schatz, G. C.; Young, M. A.; Van Duyne, R. P. (Electromagnetic Mechanism of SERS, 2006)

(untitled) - Neubrech, F.; Pucci, A.; Cornelius, T. W.; Karim, S.; García-Etxarri, A.; Aizpurua, J. (Phys. Rev. Lett., 2008)

(untitled) - Huck, C.; Neubrech, F.; Vogt, J.; Toma, A.; Gerbert, D.; Katzmann, J.; Härtling, T.; Pucci, A. (ACS Nano, 2014)

(untitled) - Moskovits, M. (Rev. Mod. Phys., 1985)

(untitled) - Kneipp, K.; Wang, Y.; Kneipp, H.; Perelman, L. T.; Itzkan, I.; Dasari, R. R.; Feld, M. S. (Phys. Rev. Lett., 1997)

(untitled) - Adato, R.; Yanik, A. A.; Amsden, J. J.; Kaplan, D. L.; Omenetto, F.; Hong, M. K.; Erramilli, S.; Altug, H. (Proc. Natl. Acad. Sci. U. S. A., 2009)

(untitled) - Lee, D.-K.; Kang, J.-H.; Lee, J.-S.; Kim, H.-S.; Kim, C.; Kim, J. H.; Lee, T.; Son, J.-H.; Park, Q.-H.; Seo, M. (Sci. Rep., 2015)

(untitled) - Lee, D.-K.; Kim, G.; Son, J.-H.; Seo, M. (Proc. SPIE, 2016)

(untitled) - Aroca, R.; Pieczonka, N.; Kam, A. P. (J. Porphyrins Phthalocyanines, 2001)

(untitled) - Milekhin, A. G.; Yeryukov, N. A.; Sveshnikova, L. L.; Duda, T. A.; Rodyakina, E. E.; Sheremet, E. S.; Ludemann, M.; Gordan, O. D.; Latyshev, A. V.; Zahn, D. R. T. (Thin Solid Films, 2013)

(untitled) - Oraevsky, A. A.; Oraevsky, A. N. (Quantum Electron., 2002)

(untitled) - Sidorov, A. N. (Opt. Spectrosc., 1976)

(untitled) - Meshkova, G. N.; Vartanyan, A. T.; Sidorov, A. N. (Opt. Spectrosc., 1977)

(untitled) - El-Nahass, M. M.; Abd-El-Rahman, K. F.; Darwish, A. A. A. (Mater. Chem. Phys., 2005)

(untitled) - Zeman, E. J.; Carron, K. T.; Schatz, G. C.; Van Duyne, R. P. (J. Chem. Phys., 1987)

(untitled) - Kötz, R.; Yeager, E. (J. Electroanal. Chem. Interfacial Electrochem., 1980)

(untitled) - Toman, P.; Nešpůrek, S.; Yakushi, K. (J. Porphyrins Phthalocyanines, 2002)

(untitled) - Milekhin, I. A.; Kuznetsov, S. A.; Rodyakina, E. E.; Milekhin, A. G.; Latyshev, A. V.; Zahn, D. R. T. (Beilstein J. Nanotechnol., 2016)

(untitled) - Neubrech, F.; Weber, D.; Enders, D.; Nagao, T.; Pucci, A. (J. Phys. Chem. C, 2010)

(untitled) - Toma, A.; Tuccio, S.; Prato, M.; De Donato, F.; Perucchi, A.; Di Pietro, P.; Marras, S.; Liberale, C.; Zaccaria, R. P.; De Angelis, F.; Manna, L.; Lupi, S.; et al. (Nano Lett., 2015)

(untitled) - D’Andrea, C.; Bochterle, J.; Toma, A.; Huck, C.; Neubrech, F.; Messina, E.; Fazio, B.; Maragò, O. M.; Di Fabrizio, E.; de La Chapelle, M. L.; Gucciardi, P. G.; Pucci, A. (ACS Nano, 2013)

(untitled) - Cherkasova, O. P. (Biochemistry (Moscow), 2007)

Hormone Assays in Biological Fluids - Holder, G. (Measurement of Glucocorticoids in Biological Fluids)

(untitled) - Cherkasova, O. P.; Selyatitskaya, V. G. (Biochemistry (Moscow), 2013)

(untitled) - Al Sharef, O.; Feely, J.; Kavanagh, P. V.; Scott, K. R.; Sharma, S. C. (Biomed. Chromatogr., 2007)

(untitled) - Lee, S.; Lim, H.-S.; Shin, H.-J.; Kim, S.-A.; Park, J.; Kim, H.-C.; Kim, H.; Kim, H. J.; Kim, Y.-T.; Lee, K.-R.; Kim, Y.-J. (J. Anal. Methods Chem., 2014)

(untitled) - Mitchell, J. S.; Lowe, T. E.; Ingram, J. R. (Analyst, 2009)

Steroid Analysis - Kasal, A.; Budesinsky, M.; Griffiths, W. J. (Spectroscopic Methods of Steroid Analysis, 2010)

(untitled) - Rojek, B.; Wesolowski, M. (J. Therm. Anal. Calorim., 2017)